2013
DOI: 10.1590/0004-282x20130174
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between sleep disorder screening and executive dysfunction in children with attention deficit-hyperactivity disorder

Abstract: Objective: To compare frequency of sleep disorders (SD) and executive dysfunction (ED) in children with attention deficit-hyperactivity disorder (ADHD) and a control group. Method: We studied 156 children with ADHD with a mean age of 8.5 years, and a control group with 111 children with a mean age of 8.3 years. We utilized the Pediatric Sleep Questionnaire (PSQ) to screen SD and the working memory measurement from the Wechsler intelligence scale for children (WISC-IV) to screen ED. Results: We did not observe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In another study ( n = 56, 6–12 years), actigraphy-measured bed time movements predicted poorer performance on the cognitive assessment subscales of vocabulary and similarities (WISC-III subtests for assessing retrieval of learned verbal information and abstract reasoning/concept formation respectively) and general memory index score (assessing immediate and short term verbal memory) on a standardized memory and learning test (Suratt et al, 2011). Zambrano-sánchez et al (2013) found correlation between the presence of specific sleep disorders and WISC-IV measurements among 7 to 12 year old children with individual subtypes of ADHD ( n = 156); children with ADHD-combined presentation showed significant correlations between periodic limb movements during sleep and coding subtest value (measuring processing speed), between obstructive sleep apnea-hypopnea syndrome and block design values (measuring Perceptual reasoning) and between inadequate sleep hygiene and digit span subtest values (measuring working memory), whereas children with ADHD-Hyperactivity showed significant correlations between sleep apnea and digit space score and inadequate sleep hygiene and block design scores; and finally, children with ADHD-Inattentive showed significant correlations between inadequate sleep hygiene and each of coding, block designs, and digits span scores (Zambrano Sanchez et al, 2013). A prospective study (birth to 8.5 years, n = 1120) found persistent regulatory problems in sleep behaviors during infancy predicted lower IQ, increased attention deficits as observed during the test situation, and considerably increased odds of a ADHD diagnosis during preschool years (Schmid & Wolke, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study ( n = 56, 6–12 years), actigraphy-measured bed time movements predicted poorer performance on the cognitive assessment subscales of vocabulary and similarities (WISC-III subtests for assessing retrieval of learned verbal information and abstract reasoning/concept formation respectively) and general memory index score (assessing immediate and short term verbal memory) on a standardized memory and learning test (Suratt et al, 2011). Zambrano-sánchez et al (2013) found correlation between the presence of specific sleep disorders and WISC-IV measurements among 7 to 12 year old children with individual subtypes of ADHD ( n = 156); children with ADHD-combined presentation showed significant correlations between periodic limb movements during sleep and coding subtest value (measuring processing speed), between obstructive sleep apnea-hypopnea syndrome and block design values (measuring Perceptual reasoning) and between inadequate sleep hygiene and digit span subtest values (measuring working memory), whereas children with ADHD-Hyperactivity showed significant correlations between sleep apnea and digit space score and inadequate sleep hygiene and block design scores; and finally, children with ADHD-Inattentive showed significant correlations between inadequate sleep hygiene and each of coding, block designs, and digits span scores (Zambrano Sanchez et al, 2013). A prospective study (birth to 8.5 years, n = 1120) found persistent regulatory problems in sleep behaviors during infancy predicted lower IQ, increased attention deficits as observed during the test situation, and considerably increased odds of a ADHD diagnosis during preschool years (Schmid & Wolke, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…There were also associations between poorer executive-cognitive functions and sleep deficits consistently reported in children with ADHD (Cremone, Kurdziel, et al, 2017; Hansen et al, 2013; Moreau et al, 2013). Cognitive functions assessed through manual/machine aided neuropsychological tests and sleep measures revealed cross sectional as well as longitudinal associations between these in ADHD (Cremone et al, 2018; Gruber et al, 2011; Kidwell et al, 2017; Saito et al, 2019; Sciberras et al, 2015; Surratt et al, 2011; Zambrano-sánchez et al, 2013). For example, Kidwell et al (2017) found longitudinal associations between sleep problems at age 3 and higher levels of inattention/hyperactivity in 4th grade predicted by higher executive functions deficits.…”
Section: Discussionmentioning
confidence: 98%
“…La gente estaba más preocupada por su salud y su familia que por el ocio y los amigos. Los resultados contribuyen a las lagunas de conocimiento de los cambios individuales a corto plazo en las condiciones psicológicas después del brote 21 . Sus resultados son congruentes con nuestros resultados.…”
Section: Discussionunclassified
“…The co-existence of ADHD and PLMS is reported to occur with a certain frequency 24 . Symptoms in children with ADHD include hyperactivity, distractibility during task performance, disorganization, inability to follow through on a plan, inability to shift set and reprogram activities when needed, and deficient rulegoverning behavior.…”
Section: Main Findingsmentioning
confidence: 99%